Exploring Outdoor Space Experience: A Study of Kopi Nako Café - Satria, Widi Dwi; Damanik, Novita Hillary Christy; Kamaruddin, Maqbul; Gharata, Verza Dillano; Rahmatullah, Ananda Dwi; Febriyanto, Prastyo Arum (Journal of Architectural Research and Design Studies, 2025)
Enjoying outdoor space in a café is not limited to the existing furniture. However, it includes all design elements that affect the way visitors feel and enjoy a comfortable space atmosphere. Kopi Nako Café in Lampung has an outdoor café concept that gives a tropical feel to the outside space of the café, which can be felt directly by visitors. The purpose of this research is to find out how the outdoor space experience at Kopi Nako Café Lampung can be felt in fulfilling the comfort of movement and the atmosphere of the built space. The research was designed using qualitative methods with field observation methods. From the findings, the outdoor area of Kopi Nako Café provides an outdoor space experience to visitors through the volume of space, through movement, seeing shapes, hearing sounds, feeling the wind, and so on. Kopi Nako Café offers attractive atmospheres and added value to visitors. The importance of the role of Kopi Nako Café's outdoor space as a whole can be said to be the main factor contributing to the attractiveness of the café and the brand image of the café. The unique design and conceptualized details create a strong visual identity and distinguish it from other cafés.